(untitled) (Journal of the College of Basic Education, 2022)
Among the important achievements that have been achieved with a great impact on human life, philosophy, and laws are the multiple cultures that depend on the knowledge of their list of events, the transformations of those ideas, and the philosophies associated with laws that continued to struggle, despite all the constants surrounding them, which are somewhat far from every change.